Exploring the Impact of Emerging Technologies on Business Models, Customer Behavior, and Workforce Implications - Urdiana Demaci (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
In this study, we investigate how new technologies affect traditional company structures, consumer habits, and the implications for the labor force. This research delves deeply into the potential of robots, blockchain, and AI to disrupt existing markets and pave the way for new forms of business and product development. The study used a qualitative strategy, which included a literature review and industry-specific case studies. According to the data and analysis, if you want to successfully adopt new technologies, you need to take a strategic approach that takes into account the wants and fears of your customers and employees while also opening the door to growth and innovation. This research emphasizes the value of learning about and catering to customers' individual preferences and requirements before investing in the creation of customer-centric technologies. In addition, it stresses the significance of businesses investing in retraining and development to equip their workforce with the skills necessary to adapt to new job roles, as well as working with the workforce to address concerns and meet their needs. Finally, to effectively utilize emerging technologies for growth and innovation, it is necessary to continually evaluate and adjust to the impact they are having on business models, customer behavior, and the workforce